Centralized Clinical Pharmacy-Drug Order Verifications in Super Speciality Hospitals: Impact on Patient Outcomes and Safety - Bhardwaj, Sourabh; Majumdar, Devarati; Nalliah, Venkatesan (Journal of Pharmacy Practice and Community Medicine, 2026)
Introduction: The Centralized Clinical Pharmacy model in multi-branch hospitals plays a pivotal role in enhancing patient safety by minimizing medication errors through the standardization of prescription review and documentation. Objectives: To evaluate the effectiveness of the centralized pharmacist oversight in identifying and correcting prescribing issues. Materials and Methods: A review of 17,255 prescription checks was conducted to assess the prevalence of medication errors. Results: The most common issues identified included therapeutic duplication, incorrect dosing, missing diluent documentation, incorrect scheduling, and incomplete administration details. High-alert medicines and antibiotics were found to carry the greatest risk of errors. Discussion: The findings of this review underscore the importance of centralized pharmacist oversight in the early identification and correction of prescribing problems. This oversight supports rational drug use and reinforces medication governance across hospital branches. Conclusion: Implementing a centralized clinical pharmacy model significantly contributes to reducing medication errors and enhancing patient safety in multi-branch hospital settings.
Keywords: Centralized Clinical Pharmacy model; High-Alert Medications; Medication Safety; Prescription Audit; Therapeutic Duplication